Assessing Fiscal Autonomy of Local Government in Nepal: A Study of Chitwan District (Shaheed Smriti Journal, 2025)
This study observes the fiscal autonomy of local governments in Chitwan District, within the framework of fiscal federalism in Nepal. The study employs a descriptive-analytical research design and relies entirely on secondary data. Fiscal autonomy is assessed using a ratio-based methodology FAR, FSR, and TTDR to evaluate internal revenue strength, expenditure-financing capacity, and dependency on intergovernmental transfers. The findings reveal persistently low fiscal autonomy in Chitwan District, as a 0.151 FAR indicates that local governments generate only 15.1 percent of total revenue from internal sources. Likewise, the 0.145 FSR shows that own-source revenues finance merely 14.5 percent of total expenditure, reflecting a limited capacity to fund services and development activities independently. In contrast, a 0.711 TDR suggests that 71.1 percent of local government revenue in Chitwan sows high degree of vertical fiscal dependence. The study concluded that increasing fiscal dependency and nominal fiscal autonomy will disturb Nepal’s evolving fiscal architecture, which will raise the question about the sustainability of the entire federal system of the country.